Utilização de Stents Revestidos com Fármaco em Angioplastia Primária - Resultados Clínicos a Longo Prazo - Fiarresga, A (2011)
INTRODUCTION: The use of drug-eluting stents in the context of mechanical reperfusion following ST-segment elevation myocardial infarction (MI) was initially viewed with concern. The main fear was that the drugs' action in unstable lesions could increase the risk of thrombotic stent occlusion. Furthermore, there was no evidence that the proven benefit of reduced instent restenosis could be extended to such patients, since they were excluded from the initial clinical trials. OBJECTIVES: To assess the safety and long-term clinical outcomes of the use of drug-eluting stents in primary angioplasty. METHODS: The first 100 consecutive and non-selected patients admitted for MI and treated by primary angioplasty with drug-eluting stent implantation in the target lesion were analyzed retrospectively. The efficacy and safety of the procedure, in-hospital clinical evolution and the occurrence of major adverse cardiac events in the first year were assessed. RESULTS: Patients' mean age was 58.2 +/- 11.5 years, and 78 were male. The success rate of primary angioplasty was 99%. Stents coated with sirolimus were used in 67 patients, paclitaxel in 19 and dexamethasone in 16. In-hospital mortality was 3%. The follow-up rate at 12 months was 98%. During this period, the rate of target vessel revascularization was 1% (with no patient requiring target lesion revascularization), MI 2%, and overall mortality 3.9%. Fourteen patients had clinical indication for repeat coronary angiography, which showed no significant in-stent restenosis. One event was considered to be due to acute stent thrombosis. The incidence of major adverse events was 5.9%. CONCLUSION: The use of drug-eluting stents in MI patients undergoing primary mechanical revascularization is safe and is associated with a reduced incidence of major adverse events, thrombosis and clinical restenosis at one year.